Ciência, conhecimento e naturalismo na filosofia de Nietzsche - JESUS, Francisco de Paula Santana de (Universidade Federal do Pará, 2024)
This dissertation aims to investigate, discuss and interpret the issue of knowledge in Nietzsche’s philosophy. To do so, we assume that the philosopher thematizes knowledge and science from a naturalist perspective, by highlighting their meta-epistemological elements (such as biological influences, or surreptitious commitments to moral values). In this sense, resorting to the natural sciences serves the philosopher as a subsidy for a non-metaphysical investigation of human modes of cognition. It is important, then, to emphasize the parallels between the Nietzschean interpretation and the studies of authors with whom Nietzsche came into contact, such as Mach, Boscovich and Ribot. This demands the study of sources as a methodological resource to determine the meaning of the notion of knowledge in Nietzsche’s philosophy. Thus, our research seeks to 1) outline a history of the notion of knowledge from The Birth of Tragedy; to, then, 2) to present the naturalists perspectives of the knowledge; and, finally, 3) interpret how the main scientific-philosophical models (the Socratic and the sophistic) were formed based on Nietzschean philosophical psychology. Finally, we offer a discourse on the notion of space implied in the Nietzschean hypothesis of the will to power.